The Influence of Generations on Career Choice (Social Cognitive Career Theory Perspective) - Prawitasari, Galuh (Universitas Negeri Padang, 2018)
The phenomenon of multigenerational labor provides new challenges in the world of career. The difference of values and objectives of each generation can influence individual’s career choice thus career counselor need an approach to be able to help clients identifying their work values. Social Cognitive Career Theory (Lent, Brown, & Hackett, 1994) is a fairly recent approach because it provides a perspective based on specific self-efficacy beliefs of each generation. Due to period differences, the values adopted between one generation with another generation have been resulted in different personal accomplishments and thus different career choices. Individual from the Traditional Generations will tend to choose careers which provide firm loyalty as his personal accomplishment, whether individual from The Baby Boomers will tend to choose careers which provide prestiges, facilities, and positions. The X Generation lay their personal accomplishments on freedom and balance between career and family. The Y Generation which known as digital natives tend to choose careers which give them freedom and creativity to work by utilizing high technology. Similiar to their former, the Z Generation not only tend to choose careers which give them freedom and creativity but also expect feedback from the experienced people.